Lung sequestration: a rare cause for pulmonary symptoms in adulthood - Gompelmann, Daniela; Eberhardt, Ralf; Heußel, Claus Peter; Hoffmann, Hans; Dienemann, Hendrik; Schuhmann, Maren; Böckler, Dittmar; Schnabel, Philipp Albert; Warth, Arne; López-Benitez, Rubén; Herth, Felix (Respiration, 2011)
Background: Lung sequestration is a rare congenital pulmonary disorder and is usually diagnosed in children with recurrent pulmonary infections. Lung sequestrations are not commonly found to be a cause of respiratory symptoms in adults. Objectives: It was the aim of this study to show that pulmonary sequestration is rare in advanced age and can be accompanied by severe pulmonary symptoms. Methods: We conducted a case series analysis of patient characteristics, symptoms, diagnosis and treatment of 11 adults with a lung sequestration at the Thoraxklinik Heidelberg between 2001 and 2009. Results: From 2001 to 2009, intralobar lung sequestration was diagnosed and treated in 11 adults aged 19 to 58 years with an average age of 39.9 ± 11.3 years and a male:female distribution of 5:6. In 3 patients (27.3%), the predominant symptom was hemoptysis. Recurrent pulmonary infections occurred in 1 patient (9.1%); pneumonia and lung abscess were detected in 2 patients (18.2%). In 3 cases (27.3%), dry cough was the predominant symptom, and in only 2 cases (18.2%), lung sequestration was asymptomatic. Eight patients (72.7%) were diagnosed by imaging techniques prior to surgery. In 3 cases (27.3%), diagnosis was made intraoperatively and by pathological examination. Surgical intervention included 7 lobectomies (63.6%), 3 wedge resections (27.3%) and 1 (9.1%) segmentectomy. Conclusion: Lung sequestration in adults is rare, but it can cause severe pulmonary symptoms. In cases of recurrent pulmonary infections of identical localization or recurrent hemoptysis, lung sequestration should be considered in order for the diagnosis to be made rapidly. Surgical resection is the treatment of choice.
Gesehen am 27.06.2022